Artikel Review: Analisis Obat Metamfetamin Dalam Sampel Rambut Dengan Berbagai Metode - Syifa Khairunnisa; Eka Wulan Galuh Pratiwi; Anggi Ayu Pratama; Marsah Rahmawati; Lina Nurfadhila (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Methamphetamine is a narcotic substance commonly known as shabu - shabu, which can damage the central nervous system and even cause death so that its distribution is restricted in Indonesia. The content of methamphetamine in the body can be analyzed using biological samples, one of which is hair. Hair is a part of the body that is commonly used to prove the presence of methamphetamine in the body because in the hair a drug can last for a long time, up to months. Writing a review of this article aims to make it easier for readers and researchers. The method of writing a review of this article is by conducting a literature search of research related to the analysis of methamphetamine in biological hair samples. Based on the results of a review of the journal, analysis of methamphetamine in hair samples can be carried out qualitatively and quantitatively with several methods that can be used to detect methamphetamine, including the marquis method, Gas Chromatography Mass Spectroscopy (GC-MS), Graphene Oxide Assisted Membrane Electron Extraction (EME) with Chromatography Gas (GC), and FE-GC/MS.